Modelling the Effects of Ageing Time of Starch on the Enzymatic Activity of Three Amylolytic Enzymes. (30th April 2012) - Guerra, Nelson P.; Pastrana Castro, Lorenzo
Abstract : The effect of increasing ageing time ( t ) of starch on the activity of three amylolytic enzymes (Termamyl, San Super, and BAN) was investigated. Although all the enzymatic reactions follow michaelian kinetics, v max decreased significantly (P < 0.05 ) and K M increased (although not always significantly) with the increase in t . The conformational changes produced in the starch chains as a consequence of the ageing seemed to affect negatively the diffusivity of the starch to the active site of the enzymes and the release of the reaction products to the medium. A similar effect was observed when the enzymatic reactions were carried out with unaged starches supplemented with different concentrations of gelatine [ G ]. The inhibition in the amylolytic activities was best mathematically described by using three modified forms of the Michaelis-Menten model, which included a term to consider, respectively, the linear, exponential, and hyperbolic inhibitory effects of t and [ G ].